INISIATIF PENGABDIAN MASYARAKAT UNTUK MENINGKATKAN KEMAMPUAN BAHASA INGGRIS MELALUI PELATIHAN TOEFL DARING - Sutarman, Sutarman; Sulistianingsih, Neny; Sudewi, Ni Ketut Putri Nila (ABIDUMASY, 2024)
This community service initiative aimed to enhance English proficiency, specifically in the context of the TOEFL test, which is crucial for measuring language competence in today's globalized world. The webinar targeted teachers and students, providing a platform for interactive learning and discussion. The methodology included delivering theoretical knowledge along with practical exercises, focusing on listening, reading, and structure components of the TOEFL. The results showed high participant satisfaction, with an average score of 4.5 on the content quality and interaction. Participants expressed interest in diverse topics for future sessions, emphasizing the importance of continuous improvement in language training programs. The findings underscore the necessity of such community service programs to foster English language skills, thereby enhancing competitive capabilities in the global educational landscape.